Kompetensi Pedagogik Guru Biologi Bersertifikasi Di Kabupaten Sikka - Yuli Mira Syafriati Y. M. Sani; Akhsanul In’am (Jurnal Kebijakan dan Pengembangan Pendidikan, 2016)
Abstract: This research aims to analyze the pedagogical competence of certified biology teachers in Sikka Regency. The method used is a descriptive quantitative method. Data collection techniques are the distribution of questionnaires and interviews. The study was conducted on certified high school Biology teachers in Sikka District. The results showed that certified Biology teachers in Sikka District had excellent pedagogical potential based on the overall average value of each teacher's core competencies, especially in aspects of mastering students' characteristics from physical, moral, spiritual, social aspects, cultural, emotional, and intellectual (4.22), develop curriculum related to the subjects (4.49), conduct assessment and evaluation of learning processes and outcomes (4.43) and utilize the results of assessment and evaluation for the benefit of learning ( 4.51). Specifically on the aspect of carrying out reflective actions to improve the quality of learning is still not good or sufficient (3.32) this is because Biology teachers have never conducted research (CAR) due to limited time and thought.Keywords: Pedagogic competence, Teacher, Biology, Certification Abstrak: Penelitian ini bertujuan untuk menganalisis kompetensi pedagogik guru biologi bersertifikasi di Kabupaten Sikka. Metode yang digunakan metode kuantitatif deskriptif. Teknik mengumpulkan data adalah penyebaran kuesioner dan wawancara. Penelitian dilakukan pada guru Biologi SMA bersertifikasi di Kabupaten Sikka. Hasil penelitian menunjukkan bahwa guru Biologi bersertifikasi di Kabupaten Sikka memiliki kompotensipedagogik yang sangat baik berdasarkan nilai rata-rata keseluruhan dari masing-masing kompetensi inti guru, terutama pada aspek-aspek: menguasai karakteristik peserta didik dari aspek fisik, moral, spiritual, sosial, kultural, emosional, dan intelektual (4,22), mengembangkan kurikulum yang terkait dengan mata pelajaran yang diampu (4,49),  menyelenggarakan penilaian dan evaluasi proses dan hasil belajar (4,43) dan memanfaatkan hasil penilaian dan evaluasi untuk kepentingan pembelajaran (4,51). Khusus pada aspek melakukan tindakan reflektif untuk peningkatan kualitas pembelajaran masih kurang baik atau cukup (3,32) hal ini dikarekan guru Biologi belum pernah melakukan penelitian (PTK) dikarenakan keterbatasan waktu dan pikiran.Kata kunci: Kompetensi pedagogik, Guru, Biologi, Sertifikasi